A standardized pathology report for gastric cancer: 2nd edition - Young Soo Park; Myeong-Cherl Kook; Baek-hui Kim; Hye Seung Lee; Dong-Wook Kang; Mi-Jin Gu; Ok Ran Shin; Younghee Choi; Wonae Lee; Hyunki Kim; In Hye Song; Kyoung-Mee Kim; et al. (Journal of Pathology and Translational Medicine, 2023)
The first edition of ‘A Standardized Pathology Report for Gastric Cancer’ was initiated by the Gastrointestinal Pathology Study Group of the Korean Society of Pathologists and published 17 years ago. Since then, significant advances have been made in the pathologic diagnosis, molecular genetics, and management of gastric cancer (GC). To reflect those changes, a committee for publishing a second edition of the report was formed within the Gastrointestinal Pathology Study Group of the Korean Society of Pathologists. This second edition consists of two parts: standard data elements and conditional data elements. The standard data elements contain the basic pathologic findings and items necessary to predict the prognosis of GC patients, and they are adequate for routine surgical pathology service. Other diagnostic and prognostic factors relevant to adjuvant therapy, including molecular biomarkers, are classified as conditional data elements to allow each pathologist to selectively choose items appropriate to the environment in their institution. We trust that the standardized pathology report will be helpful for GC diagnosis and facilitate large-scale multidisciplinary collaborative studies.